Basic biochemical characterization of cytosolic enzymes in thymidine nucleotide synthesis in adult rat tissues: implications for tissue specific mitochondrial DNA depletion and deoxynucleoside-based therapy for TK2-deficiency - Wang, Liya (BMC Mol Cell Biol, 2020)
BACKGROUND: Deficiency in thymidine kinase 2 (TK2) or p53 inducible ribonucleotide reductase small subunit (p53R2) is associated with tissue specific mitochondrial DNA (mtDNA) depletion. To understand the mechanisms of the tissue specific mtDNA depletion we systematically studied key enzymes in dTMP synthesis in mitochondrial and cytosolic extracts prepared from adult rat tissues. RESULTS: In addition to mitochondrial TK2 a cytosolic isoform of TK2 was characterized, which showed similar substrate specificity to the mitochondrial TK2. Total TK activity was highest in spleen and lowest in skeletal muscle. Thymidylate synthase (TS) was detected in cytosols and its activity was high in spleen but low in other tissues. TS protein levels were high in heart, brain and skeletal muscle, which deviated from TS activity levels. The p53R2 proteins were at similar levels in all tissues except liver where it was ~ 6-fold lower. Our results strongly indicate that mitochondria in most tissues are capable of producing enough dTTP for mtDNA replication via mitochondrial TK2, but skeletal muscle mitochondria do not and are most likely dependent on both the salvage and de novo synthesis pathways. CONCLUSION: These results provide important information concerning mechanisms for the tissue dependent variation of dTTP synthesis and explained why deficiency in TK2 or p53R2 leads to skeletal muscle dysfunctions. Furthermore, the presence of a putative cytosolic TK2-like enzyme may provide basic knowledge for the understanding of deoxynucleoside-based therapy for mitochondrial disorders.